2002
DOI: 10.1111/j.1744-7348.2002.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different soil and clove treatments in the control of white rot of garlic

Abstract: Soil solarisation was consistently efficacious in reducing inoculum density to undetectable levels in a field naturally-infested with Sclerotium cepivorum. This treatment delayed epidemic onset of white rot of garlic 2-3 months as compared with the untreated control or the inoculation of planting furrows with Glomus intraradices. Furthermore, significant reductions of disease incidence and of the standardised AUDPC were also observed in solarised plots, resulting in quantitative and qualitative yield improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This is based on the fact that 0.01-0.1 g sclerotia/g of soil resulted in infection of less than or equal to 85-100% and 100% incidence of disease in onion and garlic plants, respectively. This is sclerotia germination stimulants (diallyl disulfides, DADS), composted onion waste, host resistant were also found moderately effective at varying degrees [14][15][16]. It has been found that systemic as well as non-systemic fungicides significantly reduced garlic white rot disease development and resulted in improved garlic yield.…”
Section: Harvesting Sclerotium Cepivorum Sclerotiamentioning
confidence: 99%
“…This is based on the fact that 0.01-0.1 g sclerotia/g of soil resulted in infection of less than or equal to 85-100% and 100% incidence of disease in onion and garlic plants, respectively. This is sclerotia germination stimulants (diallyl disulfides, DADS), composted onion waste, host resistant were also found moderately effective at varying degrees [14][15][16]. It has been found that systemic as well as non-systemic fungicides significantly reduced garlic white rot disease development and resulted in improved garlic yield.…”
Section: Harvesting Sclerotium Cepivorum Sclerotiamentioning
confidence: 99%
“…Perhaps AMF compensate the damage of diseases and insect through improvement of plant health, root structure, and nutrient acquisition (Majewska et al, 2017). However, there was no significant difference between G. intraradices-colonized plants and non-AMF-colonized plants infected with white rot (Prados-Ligeo., 2002). AMF also inhibited the damage of nematode in menthol mint (Ratti et al, 2000), and reduced the damage of Pratylenchus coffea (Elsen et al, 2003).…”
Section: Heavy-metal Stressmentioning
confidence: 99%
“…Furthermore, developing a new variety having with appropriate bulb quality and disease resistance is difficult (Earnshaw et al., 2000). Other methods used to reduce Allium white rot severity such as, fungicides (Zewide et al., 2007), soil flooding (Banks and Edgington, 1989), addition of composts (Entwistle, 1990), solarization and mulching (Satour et al., 1989), incorporation of cruciferous residues (Smolinska, 2000), application of antagonists (Elshahawy et al., 2017a), and sclerotial mycoparasites (Elshahawy et al., 2017b), have been found to be moderately effective to varying degrees (Prados-Ligero et al., 2002). An effective control method has been obtained with soil partial-sterilizers such as methyl bromide, dazomet and vapam which destroy the sclerotia (Adams and Johnston, 1983), but such treatments are expensive.…”
Section: Introductionmentioning
confidence: 99%